(untitled) (The Peerian Journal, 2022)
In this article, the authors told about the history and description of ceramic vessels stored in the funds of the State Museum of History and Culture of the Jizzakh region. At the same time, they conducted a scientific analysis of ceramic products related to the Nurtep culture, studied in the Jizzakh oasis, materials of ancient and early medieval monuments of Urdatep, Kitatep, Munchoktep, Eski-Hovos, Kaliyatep, Kurgontep, as well as ceramic dishes studied in the burial grounds of nomadic pastoralists. The authors claim that scientifically based coverage of the history of pottery thus serves as a valuable resource for museum workers in explaining to museum visitors the periodical date, function and methods of making objects